AS QUEBRADEIRAS DE COCO NOS CAMPOS JURÍDICOS REGIONAIS DO MARANHÃO: as leis do babaçu livre como um direito vindo de abajo e a construção de cidadanias múltiplas. - CAVALCANTE, Ricardo Vinhaes Maluf (2020)
This dissertation intends to analyze the Free Babassu Laws, especially in the State of Maranhão, regarding the maintenance of the identity of the babassu coconut breakers and, thus, also in relation to the exercise of multiple citizenships and the constitution of a pluralist right, built from below, that is, from the struggles of social movements. This is a bibliographical research, documentary analysis regarding the Free Babaçu Laws, having as reference, other documents made available by the Interstate Movement of Coco Babaçu Breakers - MIQCB; still under the methodological bias, performs the analysis of videos, which include interviews with coconut breakers, already recorded by Prof. Dr. Joaquim Shiraishi Neto as part of his research. It is clarified that this audiovisual material is part of the collection that is being used in the production of a documentary about the subject.